Collaborative relationships development process in halal supply chain / Hasbullah Othman - Othman, Hasbullah (2021)
The successful of business in supply chain (SC) is measured via the successfulness of its collaboration between buyer and seller, whilst collaborative relationships development process (CRDP) is the best tool for measurement the successful of the collaboration itself. On the other hand, Halal supply chain (HSC) is relatively an emerging topic in SC. Despite numerous studies in collaboration in SC and HSC, there are very limited study focused on the CRDP in SC, whilst the studies in HSC are still on the fundamental of Halalan Tayyiban. Outcome of the literature reviews prompted the researcher to embark a study on CRDP in HSC with greater emphasis on Malay Muslim culture. Since Malaysia is recognised as the world’s best example of benchmarking of Halal food, the study is carried out in Halal bakery industry taking into consideration of the important of this industry in F&B in Malaysia and the issue its facing towards its Halal requirement. This study is aimed to investigate the process of CRDP in HSC; to identify the element of culture that play significant roles in the CRDP among the players in HSC; to develop a model on CRDP in HSC; and to validate the said model. This qualitative study is conducted via semi-structured in-depth interviews with twenty-four Muslim owners and personnel in SMEs and big firms in Halal bakery industry throughout Peninsular Malaysia. The model on CRDP in HSC is developed upon the tabulation of the research findings via thematic analysis, and verified by ninety practitioners and experts via questionnaires. The incorporation of CRDP into the theory of HSC, is the biggest contribution of this study. Others include; contribution on cultural aspect in term of interchangeable of identification between Malay and Muslim; contribution on searching process for potential supplier based on element of Malay as Muslim; contribution on portraying Malay identity as Halal identity; and contribution on the practice of businessman in Malaysia to search for Muslim and element of Malay. The validation results indicate the highest mean of 4.67 for dimension on ‘Malay ‘s buyer will buy goods through Halal supply’ and the lowest mean of 3.29 for dimension on ‘Malay’s buyer will not switch from the existing supplier, as a mark of commitment towards the supplier’. This reaffirmed the CRDP model that Malay Muslim will only switch, even to non-Muslim suppliers provided the new suppliers are able to supply products with Halal certificate. The findings from this study on CRDP in HSC benefited both the players and regulators in HSC industry. The Malay Muslim should take advantage of “Malay is Muslim”. As Muslim, their products are perceived Halalan Tayyiban and this is a clear advantage for marketing their products. This study also acts as a flatform for the regulators to review the practice of allowing the non-Muslim businessmen which associate their products with Malay Muslim’s name in order to gain support from Malay Muslim customers. In future, it is recommended to extend the scope of study to cover non-Malay / non-Muslim since most of the big HSC players in Malaysia are non-Malay / non-Muslim.